Efficient method for calculating molecular excitation energies by time-dependent density-functional theory - Heinze, H.H.; Görling, Andreas; Rösch, Notker (Journal of Chemical Physics, 2000)
A method based on time-dependent density functional theory (TDDFT) is used to determine excitation energies and oscillator strengths of molecules. Excitation energies of benzene and a series of linear annelated aromatic polycyclic hydrocarbons were analyzed. The method involves the use of auxiliary basis sets and describes the features and trends in excitation spectra of the aromatic hydrocarbons.